Targeting arginase-1 exerts antitumor effects in multiple myeloma and mitigates bortezomib-induced cardiotoxicity - Kavita Ramji; Tomasz M. Grzywa; Anna Sosnowska; Aleksandra Paterek; Marta Okninska; Zofia Pilch; Joanna Barankiewicz; Filip Garbicz; Katarzyna Borg; Urszula Bany-Laszewicz; Abdesamad Zerrouqi; Beata Pyrzynska; et al. (Scientific Reports, 2022)
Abstract Multiple myeloma (MM) remains an incurable malignancy of plasma cells despite constantly evolving therapeutic approaches including various types of immunotherapy. Increased arginase activity has been associated with potent suppression of T-cell immune responses in different types of cancer. Here, we investigated the role of arginase 1 (ARG1) in Vκ*MYC model of MM in mice. ARG1 expression in myeloid cells correlated with tumor progression and was accompanied by a systemic drop in ʟ-arginine levels. In MM-bearing mice antigen-induced proliferation of adoptively transferred T-cells was strongly suppressed and T-cell proliferation was restored by pharmacological arginase inhibition. Progression of Vκ*MYC tumors was significantly delayed in mice with myeloid-specific ARG1 deletion. Arginase inhibition effectively inhibited tumor progression although it failed to augment anti-myeloma effects of bortezomib. However, arginase inhibitor completely prevented development of bortezomib-induced cardiotoxicity in mice. Altogether, these findings indicate that arginase inhibitors could be further tested as a complementary strategy in multiple myeloma to mitigate adverse cardiac events without compromising antitumor efficacy of proteasome inhibitors.